Decoding Asset Turnover: Insights into Financial Dynamics of the Automotive Sector - Mubarok, Faizul; Rentika, Della; Himawan, Farras Azhar Ananda; El Ghifari, Muhammad Sheva (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2025)
Purpose: The primary aim of this research study is to explore and analyze the interrelationships among profitability, leverage, liquidity, and interest rates in the context of the asset turnover ratio within automotive companies. Method: The research employs a purposive sampling method, selecting automotive companies as the research subjects from 2018 to 2022. A panel data regression approach is utilized to analyze the data, specifically employing the Random Effect Model. Results: The results of this research show that profitability, leverage and interest rates have a significant effect on the asset turnover ratio. In contrast, this research reveals a negative relationship between liquidity and ATR. Implications: The implication of this research is that stakeholders in the automotive industry, including management, investors, and policy makers, can use the insights obtained to make informed decisions. This study also provides practical implications for optimizing asset utilization strategies in automotive companies. The research findings contribute to existing knowledge in the fields of finance and management, enriching understanding of the dynamics that shape company performance in the automotive sector. Novelty: The novelty of this research lies in its comprehensive approach to understanding complex relationships in the context of asset turnover ratios, which have not previously been revealed in the automotive sector.